Comparison the Analysis Results of Soil Improvement PVD Preloading & Stone Column Methods for Accelerating Soil Consolidation - Anneesha Fairuz; Syafwandi (Journal of World Conference (JWC), 2021)
The third runway plan for Soekarno-Hatta Airport will be right on land which is quite dominated by soft soil, which of course is very prone to large subsidence at a relatively slow time. Because the time factor is very narrow while the target is constantly being pursued, it is necessary to have an appropriate soil improvement method to overcome this problem. There are two options, (1) Prefabricated Vertical Draining (PVD) and (2) Stone Column. Both are installed in a triangle pattern at two different distances. The effectiveness analysis between the two was carried out based on references from FHWA (1983) and Priebe (1995). The final output of this final project report is the result of reduction obtained and the length of time required to achieve the degree of consolidation in accordance with the requirements, with comparisons based on the results shown by the time vs settlement curve. The author's initial hypothesis considers that the use of PVD is superior to the use of Stone Columns in this case because the decline time is faster even though the resulting decrease is not much different from that produced by Stone Column.